A pledge of love : the Anabaptist sacramental theology of Balthasar Hubmaier - Brewer, Brian C. (Studies in Christian history and thought., 2012)
"It seeks to demonstrate that for Hubmaier the rites of the church are forefront in the development of his theology, both during his early Catholic career and during his tenure as an Anabaptist pastor and teacher. The book examines the development of Hubmaier's doctrines of Eucharist, baptism and other possible signs of sacrament, concluding with a review of Hubmaier's liturgical contributions to Anabaptist worship."--Publisher's description